ANALYSIS OF PANCING ULUR (HAND LINE) AT BUNGUS OCEANIC FISHING PORT (PPS BUNGUS) PADANG WEST SUMATERA PROVINCE - Feri Sabarna Putra; Hendrik '; Lamun Bathara (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
The Research on the analysis of Hand Line was conducted in April until May 2014 in Bungus Oceanic Fishing Port Padang, West Sumatra. The aims of this study were to analyze the financial capital, feasibility and business prospects using Hand Line. The method used to this study is a survey respondents were selected through purposive sampling of Hand Line fish catcher to size fleet of 30 GT and 50 GT because sizes of the ship is more recorded in the statistics.The results of this study indicate that venture capital of Hand Line stalling for 30 GT vessels was Rp 954.980.000 and for 50 GT vessels was Rp 1.404.960.000. Investment criteria of Hand Line stalling for 30 GT vessel show value of NPV was Rp 850.279.096 - BCR was 1.22. IRR was 38.51 % and the PP was 1.82, while 50 GT vessel show NPV about Rp 841.789.240 - BCR of 1.17 - IRR of 35.59 % and the PP of 1.10. Business prospects of 30 GT vessels is better than 50 GT vessels. This shows that Hand Line stalling for 30 GT vessels is worth extended than 50 GT vessels seen from the index investment criteria.Keywords : Hand line, feasibility, investment, PPS Bungus.